Editorial - Mark Brimble; Brian Murphy (Australasian Accounting, Business and Finance Journal, 2011)
The financial planning industry is at a critical phase of its development. The industry is still in its infancy and yet the impact of financial advice is far reaching in our society. After many years of rapid, yet dislocated, growth and various controversies, the industry is embarking on a fascinating journey towards becoming a profession. Recently the move to a fee for service basis of operation, mandatory professional indemnity insurance, formal codes of conduct and higher barriers to entry in regards to educational and professional experience requirements are key signs of development of a financial planning profession for the future.